Quality of Primary Care Center Referral Letters and Feedback Reports among Sample of PHCCs in Baghdad /Al-Rusafa Health Directorate During2015 - Lujain Anwar Alkhazrajy (مجله كليه طب الكندي, 2019)
Background:The referral system constitutes a key element of health system. Effective referral system between different levels of health care delivery represents a cornerstone in addressing patients’ health needs.